# Show that 2x+1 is a factor of the polynomial 2x³+x²-6x-3.hence factorize the polynomial.

2
by marina1

2014-10-15T21:55:54+05:30

### This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
If (2x+1) is a factor of (2x³+x²-6x-3), then zero of (2x+1) will also be a zero of (2x³+x²-6x-3).
zero of (2x+1) can be found by equating it to 0.
2x+1 = 0
⇒2x = -1
⇒x = -1/2

Put x=-1/2 in (2x³+x²-6x-3). we get
(2x³+x²-6x-3)
= 2(-1/2)³ + (-1/2)² - 6(-1/2) - 3
= 2(-1/8) + (1/4) - 6(-1/2) - 3
= -2/8 + 1/4 + 6/2 - 3
= -1/4 + 1/4 + 3 - 3
= 0
Since -1/2 is also a zero of (2x³+x²-6x-3), (2x+1) is a factor of (2x³+x²-6x-3).

Factorizing:
2x³ + x² - 6x - 3
= (2x³ + x²) - (6x + 3)
=x²(2x+1) - 3(2x+1)
= (x²-3)(2x+1)

x²-3 can be further factorized as (x-√3)(x+√3)
So 2x³+x²-6x-3 = (x-√3)(x+√3)(2x+1)
are you sure that the answer is right
yes.
you can check with the examples given in your book.
2014-10-15T21:57:33+05:30
2x3 + x2 -6x-3 can be factorise as (2x +1)(x^2-3) Hence it can be prived that (2x+1) is the factor of polynomial